Dalhuisen on transnational and comparative commercial, financial and trade law. Volume 6, Financial regulation - Dalhuisen, J. H. (Jan Hendrik) (London [England] : Hart Publishing, 2022)
"... a wide-ranging, historically and comparatively very deep and comprehensive commentary, but which is also very contemporary and forward-looking on many or most of the issues relevant in modern transnational commercial, contract and financial transactions" ( International and Comparative Law Quarterly ) Volume 6 of this new edition deals with financial regulation of banks and banking activities and products. It critically reviews micro-prudential regulation, the need for macro-prudential supervision and an independent macro-prudential supervisor, the role of resolution authorities, the operation of the shadow banking system, and the extraterritorial reach and international recognition of financial regulation. The volume considers in particular the fallout from the 2008 financial crisis and the subsequent regulatory responses in the US and Europe. The complete set in this magisterial work is made up of 6 volumes. Used independently, each volume allows the reader to delve into a particular topic. Alternatively, all volumes can be read together for a comprehensive overview of transnational comparative commercial, financial and trade law."--
1. Financial Services, Financial Service Providers, Financial Risk and Financial Regulation 1.1 Financial Services and Their Regulation 1.2 International Aspects of Financial Regulation 1.3 The 2008 Financial Crisis and its Effect on Financial Regulation 1.4 The Essentials of Commercial Banking 1.5 Capital Markets. The Essentials of the Investment Securities Business and its Regulation -- 2. International Aspects of Financial Services Regulation: The Effects of Globalisation and the Autonomy of the International Capital Markets. The Developments in GATT/WTO, the EU and BIS/IOSCO/IAIS 2.1 The Globalisation of the Financial Markets and the Informal Liberalisation of Finance 2.2 The Formal Regime for the Freeing of the Movement of Goods, Services, Current Payments and Capital After World War II 2.3 The Creation of the EEC in Europe and its Evolution into the EU 2.4 The Effects of Autonomous Globalisation Forces on Financial Activity and its Regulation in the EU 2.5 Developments in the BIS, IOSCO and IAIS. The International Harmonisation of the Capital Adequacy Regime (Basel I, II and III) -- 3. The EU Regulations and Directives Concerning the Internal Market in Financial Services: Early Action, the European Passport, the 1998 EU Action Plan for a Single Market in Financial Services, and Further Action Following the 2008 Financial Crisis 3.1 Early EU Concerns and Action in the Regulated Financial Service Industries 3.2 The Early EU Achievements in the Regulation of Financial Services 3.3 The European Passport for the Financial Services Industry 3.4 The 1998 EU Action Plan for Financial Services 3.5 The Details of the Third Generation Directives and Their Revamping Under the 1998 Action Plan. The Period up to the 2008 Financial Crisis and the Continuation of the Basic Framework 3.6 Other EU Regulatory Initiatives in the Financial Area 3.7 The EU During and After the 2008 Financial Storm -- 4. The European Banking Union -- 5. Summary, Evaluation and Conclusion
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Banking law; Financial services industry -- Law and legislation; Commercial law; Electronic books